A Pragmatic Stylistic Analysis of George Lucas’s Star Wars Original Trilogy through the Lens of Relevance Theory - Achmad, Zakaria; Lubis, Reza Dian Irawan; Aria, Fahri Mulia; Rangkuti, Rahmadsyah (Journal of English Language and Education, 2025)
This study explores the application of Relevance Theory to the pragmatic stylistic analysis of the Star Wars Original Trilogy (Episodes IV–VI). Using film transcripts as primary data, two researchers conducted a qualitative analysis of the dialogue and narrative elements. By coding for implicature, presupposition, cognitive efficiency, and audience engagement, the study reveals that the films employ subtle linguistic strategies that enhance narrative depth and foster active viewer interpretation. Notable moments—such as Darth Vader’s “Search your feelings, you know it to be true”—demonstrate how implicit meanings are skillfully embedded within the dialogue. The findings underscore the importance of indirect communication in cinematic storytelling and offer a robust framework for further research in film discourse analysis.